Bibliometric analysis of lean and green healthcare integration using Publish or Perish (PoP) - Febianti, Evi; Ilhami, M. Adha; Ekawati, Ratna; Setiawan, Hadi (Universitas Sultan Ageng Tirtayasa, 2024)
Lean Healthcare is an approach to management systems that can change the mindset of hospitals, making healthcare more organized by reducing waste. Waste can be defined as any activity that does not add value to a process. The study recommends a bibliometric analysis of this problem. This is necessary to identify research trends or gaps that still exist. Data searches use Publish or Perish software, while data analysis uses VOSviewer software. The search results and data analysis suggest that trends for Lean Healthcare problems will likely be resolved by integration with green practices. The final process can be carried out considering environmental sustainability factors.